Management of Facilities and Infrastructure in Efforts to Improve the Quality of Learning at a Public Junior High School - Marlina Marlina; Sariakin Sariakin; Musdiani Musdiani (Journal of Educational Sciences, 2026)
This study examines the management of school facilities and infrastructure and its contribution to improving learning quality at SMP Negeri 1 Baitussalam, Aceh Besar Regency. Effective management of educational facilities is essential to support the teaching and learning process and achieve better learning outcomes, although in many schools it is still limited to administrative compliance rather than educational effectiveness.  This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with the principal, vice principal for facilities and infrastructure, and teachers, supported by observation and documentation. Data analysis involved data condensation, data display, and conclusion drawing, while validity was ensured through source triangulation.  The findings reveal that the planning, procurement, inventory, and maintenance of facilities were conducted systematically and in accordance with national education standards. Such effective management fosters active learning environments, enhances student motivation, and improves overall learning quality.  In conclusion, well-planned and systematic management of school facilities and infrastructure significantly contributes to enhancing the quality of learning.